Tradiční profese, etnonyma a meziskupinové hranice Romů mluvících jihocentrální romštinou v Maďarsku. Pokus o klasifikaci veršendských Romů - Bodnárová, Zuzana (Romano džaniben, 2011)
The paper attempts to classify the Romani community of Versend (Hungary). The presented classification is based on the traditional occupations and the ethnonyms used by the Roma of Versend. These are compared with the occupations and ethnonyms of other South Central Romani speakers. The author identifies three main traditional occupations of the Versend Roma: musicians, grinders and blacksmiths. In addition, the examined linguistic groups often call themselves by professionyms based on these occupations. The author finds that the Roma of Versend feel the belonging to the linguistically assimilated musicians. The presented data in particular come from the recordings acquired during a fieldwork among the communities speaking Southern Central Romani in Hungary, which has been carried out by the author since 2008.